The Effect of Knowledge and Ease of Use on Decisions to Use QRIS Digital Payment Among Gen Z in Bandung City - Ratu Hedy Syahidah Budiarti (CAKRAWALA : Management Science Journal, 2025)
This study aims to determine the effect of knowledge and ease of use on the decision to use QRIS digital payment among Gen Z in Bandung City. The population in this study is the people of Bandung City who belong to Generation Z. Primary data was collected by questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study using the SPSS ver. 25 data analysis tool. 25. Sampling as many as 100 respondents who belong to generation Z in Bandung City. The results showed that knowledge has a positive and significant effect on usage decisions, ease of use has a positive and significant effect on usage decisions, knowledge and ease of use have a positive and significant effect on usage decisions simultaneously.